Developing WinXPRO: a software for determination of the multipole‐model‐based properties of crystals. (1st December 2014) - Stash, Adam I.; Tsirelson, Vladimir G.
<x xml:space="preserve">Abstract</x> The new release of the computer program package WinXPRO v.3x for determination of the crystal properties from parameters of the multipole‐modeled experimental electron density and anharmonic atomic displacement coefficients is described. The set of properties is significantly extended by using the density functional and information theories. In addition, a built‐in multi‐functional viewer and programs to display the output data, including the mapping of the chosen functional bonding descriptors onto surfaces of the other properties, are included.